The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/ppj2.20026
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of image georeferencing strategies for agricultural applications of small unoccupied aircraft systems

Abstract: Small unoccupied aircraft systems (sUAS) are becoming popular for mapping applications in agriculture, and photogrammetry software is available for developing orthorectified imagery and three-dimensional surface models. Ground control points (GCPs), which are objects or locations with known geographic coordinates, may be required for accurate image georeferencing. However, few studies have compared global position equipment among sUAS or investigated the effects of GCP number or arrangement on georeferencing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Ground control points (GCPs) were collected using two paired Emlid Reach RS2+ (Emlid Tech Korlátolt, Budapest, Hungary) devices, where one device was placed on a fixed, permanent base location and the other was used as a rover to collect the GPS data for each GCP. Because prior research has demonstrated that four accurate and precise GCPs near the corners of each flight mission are sufficient to georeference photogrammetry projects, that is the number that was used in this study ( Pugh et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Ground control points (GCPs) were collected using two paired Emlid Reach RS2+ (Emlid Tech Korlátolt, Budapest, Hungary) devices, where one device was placed on a fixed, permanent base location and the other was used as a rover to collect the GPS data for each GCP. Because prior research has demonstrated that four accurate and precise GCPs near the corners of each flight mission are sufficient to georeference photogrammetry projects, that is the number that was used in this study ( Pugh et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Despite direct georeferencing being possible with the onboard-RTK, the use of some GCPs is recommended for full accuracy. In the case of small square mapping extents, at least four GCPs are recommended [63]. For larger extents, at least one additional GCP is recommended in the central area [64,65].…”
Section: Uas Data Stitchingmentioning
confidence: 99%
“…More specifically, GCPs are often laid out around the perimeter as most distortion occurs in these areas during model construction (Gabrlik, 2015;Sanz-Ablanedo et al, 2018). It is important to note, that having more GCPs that are evenly dispersed increases horizontal and vertical georeferenced accuracy of the spatial data products (DTM/DSM models, orthomosaic images, or point clouds) (Pugh et al, 2021). For example, in the works of Forlani et al, (2019), implementing just one GCP decreased error from 10 cm to 3 cm.…”
Section: Direct and Indirect Georeferencing In Sfm Photogrammetrymentioning
confidence: 99%